Методика расчета равновесного количества фаз при синтезе материалов системы MgO – Al₂O₃ – SiO₂ - Логвинков, Сергей Михайлович; Кобзин, В. Г.; Шабанова, Галина Николаевна; Корогодская, Алла Николаевна; Христич, Елена Валерьевна (Національний технічний університет "Харківський політехнічний інститут", 2015)
В статье приведен способ определения начальных концентраций реагентов твердофазных реакций в системе MgO – Al₂O₃ – SiO₂ по заданному оксидному составу шихты для синтеза материалов. Предложена методика расчета параметра λ-координат твердофазных реакций, протекающих при синтезе материалов системы MgO – Al₂O₃ – SiO₂. Рассчитанные для заданного оксидного состава шихты значения координат твердофазных реакций полностью определяют равновесные концентрации фаз при прогнозируемых температурах синтеза материалов.

The paper presents a method for determining the initial concentration of the reactants in the solid phase reaction system MgO – Al₂O₃ – SiO₂ oxide for a given composition of the charge for the synthesis of materials. The main technological problem – forecasting qualitative and quantitative composition of phases in the synthesized materials based on quantitative content of the starting oxides in the raw material mixture. This qualitative and quantitative composition of the phases set microstructure and mechanical properties of synthesized materials. The method of calculation of the parameter λ-coordinates of solidphase reactions that occur in the synthesis of materials of MgO – Al₂O₃ – SiO₂. The system of equations is advantageously carried out using automated computer programs (MathCad), which greatly simplifies the process of calculating. Calculated for a given oxide composition of the charge coordinate values of solid state reactions completely determine the equilibrium concentration phase at temperatures projected synthesis of materials.
Methods of calculating the equilibrium number of phases in the synthesis of materials MgO – Al₂O₃ – SiO₂
Keywords: реакция твердофазная; координата реакций; концентрация; solid-phase reactionm; coordinate responses; concentration